Sentiment analysis of face-to-face learning based on social media - Batubara, Hendra Saputra; Ambiyar, Ambiyar; Syahril, Syahril; Fadhilah, Fadhilah; Watrianthos, Ronal (Universitas Negeri Padang, 2021)
The use of restricted face-to-face learning during the epidemic in Indonesia was discussed not just by education and health professionals, but also on social media. The study used the Twitter dataset with the keywords 'school' and 'face-to-face' to examine public opinion about face-to-face learning. The research data was obtained from Twitter utilizing Drone Emprit Academic, and it was then processed using the Naive Bayes method to create sentiment analysis. During that time, research revealed that 32% of people were positive, 54% were negative, and 14% were indifferent. Because of worries about the dangers associated with the use of face-to-face learning, negative attitudes predominate.